Emerging Roles of GDF15 in Metabolic and Cardiovascular Diseases - Tian Tian; Monan Liu; Peter J. Little; Hans Strijdom; Jianping Weng; Suowen Xu (Research)
Growth differentiation factor 15 (GDF15), a TGF-β superfamily member and stress-responsive cytokine, plays a critical role in metabolism and regulation of inflammation. This review summarizes the expression, distribution, structure, processing, and secretion of GDF15. We also discuss multilayered regulatory networks governing GDF15 expression, including ATF4/CHOP, AMPK, EGR1, EZH2, PPARγ, NRF2, ERRγ, and p53, as well as posttranscriptional regulator CNOT6L. The GFRAL receptor is central to its function, mediating the anorexigenic and metabolic effects of GDF15. This review synthesizes evidence linking GDF15 to obesity, diabetes, cardiovascular diseases, metabolic liver disorders, cachexia, sarcopenia, and aging while exploring its interactions with key metabolic factors including FGF21, GLP-1, leptin, and glucocorticoids. Lifestyle interventions such as ketogenic, high-fat diets, and exercise modulate GDF15 levels, underscoring its role in pan-metabolic health. Pharmacologically, various agents—including anti-hyperglycemic agents and natural compounds—induce GDF15 expression, implicating their therapeutic potential in cardiometabolic diseases. We comprehensively evaluate current advances in GDF15-targeted drug development, including monoclonal antibodies, fusion proteins, and small-molecule drugs, to provide a scientific foundation for innovative therapies. Finally, we outline unresolved issues in GDF15 biology and therapeutics, such as the exploration of peripheral receptors, contradictory findings in studies of cardiometabolic diseases, and the persistent challenges in developing GDF15-targeted therapeutics.